Genome-wide DNA promoter methylation and transcriptome analysis in human adipose tissue unravels novel candidate genes for obesity. - Keller, M.; Hopp, L.; Liu, X.; Wohland, T.; Rohde, K.; Cancello, R.; Klos, M.; Bacos, K.; Kern, M.; Eichelmann, F.; Dietrich, A.; Schon, M. R.; et al. (Mol Metab, 2017)
OBJECTIVE/METHODS: DNA methylation plays an important role in obesity and related metabolic complications. We examined genome-wide DNA promoter methylation along with mRNA profiles in paired samples of human subcutaneous adipose tissue (SAT) and omental visceral adipose tissue (OVAT) from non-obese vs. obese individuals. RESULTS: We identified negatively correlated methylation and expression of several obesity-associated genes in our discovery dataset and in silico replicated ETV6 in two independent cohorts. Further, we identified six adipose tissue depot-specific genes (HAND2, HOXC6, PPARG, SORBS2, CD36, and CLDN1). The effects were further supported in additional independent cohorts. Our top hits might play a role in adipogenesis and differentiation, obesity, lipid metabolism, and adipose tissue expandability. Finally, we show that in vitro methylation of SORBS2 directly represses gene expression. CONCLUSIONS: Taken together, our data show distinct tissue specific epigenetic alterations which associate with obesity.
Keywords: Adipogenesis; Adipose Tissue/*metabolism; Aged; CpG Islands/genetics; DNA Methylation/genetics; Epigenesis, Genetic/genetics; Epigenomics; Female; Gene Expression; Gene Expression Profiling/methods; Genome-Wide Association Study; Humans; Intra-Abdominal Fat/metabolism; Male; Middle Aged; Obesity/*genetics; Promoter Regions, Genetic/genetics; RNA, Messenger/genetics; Subcutaneous Fat/metabolism